Effect of Ambient Aging on Inhibition of Oxygen Reduction by Chromate Conversion Coatings - Zhang, W.; Buchheit, R.G. (Corrosion (Houston, Tex.), 2003)
ABSTRACTSoluble chromates and chromate conversion coatings (CCCs) are used to enhance corrosion resistance of aluminum alloys.1 However, chromates are toxic and carcinogenic, and it is expected that their use will be banned in the future. Despite the wide usage of CCCs, elements of chromate corrosion protection have not been fully described. For this reason, there has been increased interest in understanding how chromates and CCCs promote corrosion resistance and paint adhesion so that they might be replaced with functionally equivalent, environmentally friendly substitutes. On the basis of recent studies, CCC corrosion protection appears to be due to several different components. These include suppression of anodic reactions,2-3 suppression of cathodic reactions,4 and self-healing.5 CCCs consist largely of insoluble chromium hydroxides, which prevent contact of the environment with the substrate. In this sense they also provide barrier protection.6 Soluble chromates inhibit oxygen reduction on aluminum and lower the corrosion rate under free corrosion conditions in aerated aqueous chloride solutions.7 Oxygen reduction reaction (ORR) inhibition appears to be a result of monolayer coverage of metal surfaces by Cr(III) hydroxide, which is adsorbed and reduced from solution containing soluble Cr(VI).2,8-9 Reports on ORR inhibition by CCCs are mixed. Clark and McCreery observed that a monolayer of chromate reduction product suppressed ORR,8 and it